Long-Term Patient-Reported Quality of Life After Stereotactic Body Radiation Therapy for Recurrent, Previously-Irradiated Head and Neck Cancer - Thomas, Joel; Wang, Hong; Clump, David A.; Ferris, Robert L.; Duvvuri, Umamaheswar; Ohr, James; Heron, Dwight E. (Frontiers in Oncology, 2020)
Objectives: Long-term quality-of-life data following stereotactic body radiation therapy (SBRT) for recurrent head and neck cancer (rHNC) is underreported. We report patient-reported quality-of-life (PR-QOL) after at least 1 year post-treatment. Methods and Materials: A retrospective review was performed on 64 patients receiving SBRT for previously-irradiated rHNC. PR-QOL was prospectively evaluated using the University of Washington Quality of Life Questionnaire. The mixed effects proportional odds model was used to assess post-treatment overall PR-QOL changes, as well as the effects of late toxicities, tumor volume > 25 cc, local failure, nodal recurrence, distant failure, prior neck dissection, performance status other than ECOG 0 or Karnofsky 100, sex, age > 65, squamous vs. non-squamous primary histology, and specific organ recurrence. Results: SBRT had no significant effect on overall PR-QOL at days 1-90 post-treatment (SBRT effect 0.035, p = 0.93) and days 91-365 (SBRT effect -0.30, p = 0.45). Beyond day 365, overall PR-QOL was significantly worse than baseline (SBRT effect -0.77, p = .03). Grade ≥3 late toxicities (p = 0.0072) and tumor volume > 25 cc (p = 0.032) predicted significantly worse overall PR-QOL. Oral cavity recurrence predicted significant decrements in chewing (p = 0.0006), swallowing (p = 0.0301), and taste PR-QOL (p = 0.02). Nasal recurrence predicted significant decrements in taste PR-QOL (p = 0.030). Grade ≥3 late dysphagia predicted significant decline in chewing (p = 0.039) and swallowing (p = 0.0004). Grade ≥3 late osteonecrosis predicted significant differences in pain PR-QOL (p = 0.0026). Conclusion: PR-QOL across several domains declines immediately after SBRT for previously-irradiated rHNC before returning to baseline levels at one year. Long-term PR-QOL declines thereafter. Patients with grade ≥3 late toxicities or tumor volume >25 cc report reduced long-term overall PR-QOL, likely representing late disease progression. Specific organ recurrence and grade ≥3 late toxicities predict decrements in specific PR-QOL domains.